Some Statistical Aspects of Major Operational Incentive Schemes in Indian Schools - Singh, Virendra P. (JOURNAL OF INDIAN EDUCATION, 2012)
This paper considers some statistical aspects of major operational incentive schemes prevailing to attract children in the Indian schools. Attempts have been made to analyse the availability of major incentive schemes in the schools, such as schemes on free uniforms, free textbooks, attendance scholarship for girls, mid-day meals at primary stage in the country. The present paper is based mainly on secondary data on school education collected during Seventh All India School Education Survey conducted by the National Council of Educational Research and Training under administrative and financial control of Government of India.